THE IMPORTANCE OF LEARNING ENGLISH IN MODERN SOCIETY - Ramazonova Sitora Qurbon kizi (International Journal of Literature and Language Studies, 2026)
English has become one of the most important languages in the modern world. It is widely used in education, business, science, technology, tourism, and international communication. The ability to speak and understand English provides individuals with greater access to information, educational opportunities, and professional development. This article examines the significance of learning English in contemporary society and analyzes its role in personal, academic, and career growth. The study highlights the benefits of English language proficiency and discusses its contribution to global communication. The findings indicate that English plays a crucial role in connecting people from different cultural and linguistic backgrounds and remains an essential skill for success in the twenty-first century.